2009
DOI: 10.1177/0009922809335321
|View full text |Cite
|
Sign up to set email alerts
|

Once-Daily Atomoxetine for Treating Pediatric Attention-Deficit/Hyperactivity Disorder: Comparison of Morning and Evening Dosing

Abstract: In this 3-arm, randomized, double-blind trial, once-daily morning-dosed atomoxetine, evening-dosed atomoxetine, and placebo were compared for treating pediatric attention-deficit/hyperactivity disorder (ADHD). Patients received morning atomoxetine/evening placebo (n = 102), morning placebo/evening atomoxetine (n = 93), or morning placebo/evening placebo (n = 93) for about 6 weeks. Core symptom efficacy was measured at weeks 0, 1, 3, and 6. Parent assessments of the child's home behaviors in the evening and ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 6 publications
1
47
0
Order By: Relevance
“…In the 6-week study there appeared to be a linear reduction with no suggestion of plateau at 6 weeks (Martényi et al, 2010). In a further placebo RCT 6-week study (not in treatment-naïve patients) comparing morning and evening dosing, measuring change in the ADHD-RS total score, both cohorts showed continuing improvements until week 6 with no evident plateau, with an effect size in the morning dosing group of 0.7; evening dosing was not significantly different to placebo on this measure (Block et al, 2009). A Japanese placebo RCT using three doses also suggested no plateau at 8 weeks with two out of three doses; however, only the 1.8 mg/kg cohort separated from placebo (Takahashi et al, 2009).…”
Section: Time To Full Response Randomised Double-blind Studies Threementioning
confidence: 84%
See 3 more Smart Citations
“…In the 6-week study there appeared to be a linear reduction with no suggestion of plateau at 6 weeks (Martényi et al, 2010). In a further placebo RCT 6-week study (not in treatment-naïve patients) comparing morning and evening dosing, measuring change in the ADHD-RS total score, both cohorts showed continuing improvements until week 6 with no evident plateau, with an effect size in the morning dosing group of 0.7; evening dosing was not significantly different to placebo on this measure (Block et al, 2009). A Japanese placebo RCT using three doses also suggested no plateau at 8 weeks with two out of three doses; however, only the 1.8 mg/kg cohort separated from placebo (Takahashi et al, 2009).…”
Section: Time To Full Response Randomised Double-blind Studies Threementioning
confidence: 84%
“…In none of the recent studies was a plateau reported for ATX clinical effects at or before 6 weeks (Block et al, 2009;Martényi et al, 2010;Montoya et al, 2009;Newcorn et al, 2009;Svanborg et al, 2009), with data somewhat supportive that time to optimal response may be at least 12 weeks. A critical finding in the treatment-naïve studies (Martényi et al, 2010;Montoya et al, 2009;Svanborg et al, 2009) was that effect size of ATX was greatest at study completion (6, 10, and 12 weeks, respectively), and in the Montoya study showed no sign of plateau even at 12 weeks (Montoya et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although there are reports of insomnia as an adverse event with atomoxetine [57], multiple trials in ADHD have noted somnolence to be much more common [58], especially during the early stages of a trial or if the titration is too rapid [59]. However, somnolence can be minimized with evening administration, although daytime efficacy may be decreased [59].…”
Section: Nonstimulant Effects On Sleep: Atomoxetine and Alpha-2 Agonistsmentioning
confidence: 99%